Identifying house elements for Smart Home Appliances (SHA) adaptation in future homes of Malaysia: the research methodology / Ahmad Azmin ... [et al.] - Azmin, Ahmad; Ahmad, Nur Azfahani; Abdul Aziz, Mohamed Nizam; Abdul Razak, Ahmad Haqqi Nazali (2022)
Currently, global homeowners have encountered modern and sophisticated electrical appliances that ease their daily domestic lifestyles, including cooking, washing, and other household chores. The advancement of these technologies in the domestic sector has led to easier and more convenient lifestyles, which create a high-technology lifestyle for homeowners, which leads to complexity in house design and the need for advancement in house element integration for smart use in the house. However, the issue of adaptation of the newest appliances with the current house elements is minimally being explored, since most researchers are more focusing on the smart house concept, rather than focusing on typical houses that need to be integrated with these smart appliances. There is a need to determine the significant locations inside these typical houses that will provide an efficient and strategic way of incorporating the house elements according to the needs of the appliances. The latest Smart Home Appliances (SHA) may have various sizing, weight, and function, which can be controlled remotely through the Internet of Things (IoT), where these appliances need a proper location to receive better networking coverage. Therefore, this paper seeks to discuss a research methodology in identify significant house elements for SHA adaptation in future typical homes. An exploratory mixed-method research design has been selected for this paper involving (i) survey research which distributed questionnaires to a panel of experts and (ii) a case study with the aid of systematic observation. An observation checklist has been derived from the panel of expert results in listing the current trend of house elements. Consequently, this paper will assist related researchers in making informed decisions about method selection and deployment in their related study towards finding the best solution to adapt these SHA at a typical house in Malaysia.